ADVERSE CHILDHOOD EXPERIENCE, SOCIAL SUPPORT AND RELAPSE AMONG RECOVERING RESIDENTS OF SELECTED DRUG REHABILITATION CENTERS IN CEBU PROVINCE: A MEDIATED REGRESSION ANALYSIS - Monteros, Raymar Luke, Yrog-irog, Ronald C. , (Chelonian Research Foundation, 2024)
This research probes into the interplay between Adverse Childhood Experiences (ACE), risk of relapse, and social support among Cebuano recovering residents in selected drug rehabilitation centers in Cebu. The primary objective is to explore how ACE relates to relapse risk and whether social support mediates this relationship. Participants are aged 18-59 which according to the Dangerous Drugs Board with the highest number of lifetime users. A total of N-119 participated in the study. Findings reveal a significant portion of participants reported low perceived social support (50.4%), with most having high ACE scores (61.3%) and moderate to high risk of relapse (77.3%). Spearman correlation analysis showed no significant link between ACE and relapse risk. Additionally, ACE did not directly predict relapse risk or perceived social support, but higher social support levels were associated with reduced relapse risk. The study underscores the critical role of perceived social support in mitigating relapse risk among recovering individuals, despite ACE's limited direct impact. These insights inform the importance of bolstering social support networks in substance use disorder recovery programs.